5GEx: realising a Europe‐wide multi‐domain framework for software‐defined infrastructures. Issue 9 (29th July 2016) - Bernardos, Carlos J.; Gerö, Balázs Péter; Di Girolamo, Marco; Kern, András; Martini, Barbara; Vaishnavi, Ishan
Abstract: Market fragmentation has resulted in a multitude of network and cloud/data center operators, each focused on different countries, regions and technologies. This makes it difficult and costly to create infrastructure services spanning multiple domains, such as virtual connectivity or compute resources. In this article, we discuss the goals and work being done within the 5GEx (5G Exchange) project in realising a Europe‐wide multi‐domain platform. This platform aims at enabling cross‐domain orchestration of services over multiple administrations or over multi‐domain single administrations in the context of emerging 5G networking. The 5GEx vision is based on introducing a unification via network function virtualisation/software‐defined networking compatible multi‐domain orchestration for networks, clouds and services. We describe the motivation and 5GEx vision, the adopted architecture and the next steps in terms of implementation and experimentation. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This article presents the work being carried out by 5G Exchange project to create a multi‐provider orchestration framework and deploy it as an enabler platform into its pan‐European sandbox to reduce anything as a service creation time from 90 days to 90 min.